Impact of moderate or severe left ventricular outflow tract calcification on clinical outcomes of patients with severe aortic stenosis undergoing transcatheter aortic valve implantation with self- and balloon-expandable valves: a post hoc analysis from the SOLVE-TAVI trial - Farhan, Serdar; Stachel, Georg; Desch, Steffen; Kurz, Thomas; Feistritzer, Hans-Josef; Hartung, Philipp; Eitel, Ingo; Nef, Holger; Doerr, Oliver; Lauten, Alexander; Landmesser, Ulf; Sandri, Marcus; et al. (EuroIntervention, 2022)
Background: Left ventricular outflow tract (LVOT) calcification has been associated with worse outcomes in patients undergoing transcatheter aortic valve implantation (TAVI) and may influence the selection of prosthetic valve type. Aims: We aimed to evaluate the impact of LVOT calcification on outcomes after TAVI with a self-expanding valve (SEV) versus a balloon-expandable valve (BEV). Methods: Patients of the SOLVE-TAVI trial, randomised to Edwards SAPIEN 3 or Medtronic Evolut R, were divided according to LVOT calcification into no/mild (≤1 calcium nodule extending <5 mm and covering <10% of the LVOT perimeter) and moderate/severe LVOT calcification groups. The primary endpoint was a composite of death, stroke, moderate/severe paravalvular regurgitation, permanent pacemaker implantation and annulus rupture at 30 days. Additional endpoints included all-cause and cardiovascular mortality at 1 year. Results: Out of 416 eligible patients, moderate/severe LVOT calcification was present in 143 (34.4%). Moderate/severe LVOT calcification was associated with significantly longer fluoroscopy time and higher rates of pre- and post-dilation. Regardless of the LVOT calcification group, there was no significant difference in the primary endpoint associated with the valve type (no/mild LVOT calcification group: SEV 25.0% vs BEV 27.0%; hazard ratio [HR] 1.10, 95% confidence interval [95% CI]: 0.68-1.73; p=0.73 and moderate/severe LVOT calcification group: SEV 25.0% vs BEV 19.4%; HR 0.76, 95% CI: 0.38-1.61; p=0.49), no significant interaction between LVOT calcification and valve type (pint=0.29) and no differences between SEV vs BEV within LVOT calcification groups regarding 1-year all-cause and cardiovascular mortality. Conclusions: Moderate/severe LVOT calcification was associated with longer fluoroscopy time and an increased need for pre- and post-dilation, but not with a higher incidence of early and mid-term adverse clinical outcomes, regardless of valve type. (ClinicalTrials.gov: NCT02737150)
Gesehen am 26.04.2023